미니돼지에서 다능성 피부유래 전구세포의 추출과 이의 다배엽 세포로의 분화유도에 대한 연구 - 최문정(Moon-Jeong Choi); 변준호(June-Ho Byun); 강은주(Eun-Ju Kang); 노규진(Gyu-Jin Rho); 김종렬(Jong-Ryoul Ki)m; 김욱규(Uk-Kyu Kim); 박봉욱(Bong-Wook Park) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2008)
There are increasing reports regarding regeneration of the defected tissues using tissue engineering technique. In this technique, multipotential stem cells are essential. There are many potential sources of adult stem cells, such as bone marrow, umbilical cord blood, fat, muscle, dental tissues and skin. Among them, skin is highly accessible and easily obtained with a minimum of donor site complications. Moreover, skin is an abundant adult stem cell sources and has the potential for self-replication and immune privilege. In this study, we isolated skin-derived precursor cells (SKPs) from the ear of adult miniature pigs. In these SKPs, the expression of transcriptional factors, Oct-4, Sox-2, and Nanog were detected by RT-PCR. In vitro osteogenesis and adipogenesis were observed at 3 weeks after transdifferentiations as assayed by positive von Kossa and Oil-red O staining, respectively. In addition, expression of osteocalcin and osteonectin in the osteogenic differentiation medium and PPARγ2 and aP2 in the adipogenic differentiation medium were detected by RT-PCR. In vitro neurogenesis of porcine SKPs was observed during 24 and 72 hours after treatment of neurogenic differentiation medium. The results of this study suggest that SKPs demonstrate the properties of pluripotence or multipotence and multi-lineage differentiation. This indicates that autogenous SKPs are a reliable and useful source of adult stem cells for regenerative medicine. KCI Citation Count: 4